Estimation of variation in Vapour Liquid Equilibrium constants for modeling a multicomponent crude distillation column. Issue 13 (2016) - Muralidharan, Ganesh; Abraham, Anuj; Pappa, N.
Abstract: In this paper, the mathematical model of a multicomponent crude distillation column is investigated which aimed at predicting the concentration (mole fraction) of any component on each tray of the column. In literature, it is observed that there is a drastic up and down variations in the steady state composition profile of various multicomponent at each tray of the column. These variations are due to the assumption that Vapor Liquid Equilibrium (VLE) ratios are kept constant throughout the tray for any component and are not true in real time petroleum industries. The proposed method shows a proper procedure for choosing equilibrium constants by using an estimation technique by reverse calculation of Thomas algorithm. Hence, a reverse calculation is performed using a Tridiagonal matrix method for estimating the VLE values from the steady state composition profile for each component mixture. Further, the composition profile for various components, mainly Whole Naphtha, Straight Run Kerosene (SRK), Light Diesel Oil (LDO), Heavy Diesel Oil (HDO) and Atmospheric Residue (AR) are estimated and compared. This modified algorithm is a simple technique for ideal and non-ideal systems with ease of implementing a composition profile for a multicomponent mixture and reduction in computational complexities.